ANALOGIC NON-PROPERLY PREPARED TEACHERS VERSUS NOISY CONTAMINATED OPTICAL CHARACTER RECOGNITION REGARDING STUDENTS’ ACADEMIC PERFORMANCE, ADOPTING ARTIFICIAL NEURAL NETWORKS’ MODELING - M. H. Mustafa1, Hassan; Mohamed I. A. Ibrahim; Hany S. Ramzy (International Journal of Multidisciplinary Research and Studies, 2022)
This Research paper tackles an important and interestingly complex, and challenging educational problematic phenomenon. Specifically, it addresses two analogously interrelated issues namely: the non-properly prepared teachers that are characterized by the undesirable impact on students’ academic achievement inside classrooms. Additionally, Herein, this issue is shown to be analogous to the recognition process of noisy contaminated Optical Character Recognition (OCR). Briefly, this comparative study objectively illustrates the analogous relationship between contaminated noisy information provided by the non-properly prepared teaching process versus the noisy contaminated (OCR) process. In more detail, various noisy power level values which changed in the learning environment resulted in considerable correspondence with different learning rate values. The unfavorable amount of teacher’s improperness is mapped similar to well-known communication technology term namely signal to noise (S/N) ratio. Which quantitatively measures the clarity degree related to received desired learning/teaching signal across the educational communication channel. In other words, it illustrates simulated outcomes presented as a percentage of lessons’ focusing degree versus # Neurons for different learning rate values. More properly. The performance of non-properly prepared teachers results in noisy information submitted to children’s brains in classrooms. Accordingly. it observed annoyance in the learning environment and negatively affects the quality of children’s learning performance. Herein, this research work illustrates specifically the analogy between learning under a noisy data environment in Artificial Neural Networks (ANNS) models versus the effect of the physical environment on the quality of education in classrooms. The observed non-properly prepared teachers’ phenomenon in classrooms was observed to have a negatively undesired effect on the evaluated educational process performance. Analogously, the observed effect of additively contaminating noise power on any map size made with the resolution of (3x3) pixels. These pixels were associated with diverse three English clear characters (T&L, or H) which were originally written over (3x3) binary (black & white) digitized retina. Herein; obtained interesting findings shaded light over more complex challenging research directions towards future more elaborated investigational study for such interdisciplinary observed educational phenomena